EFFORTS TO ENSURE THE IMPLEMENTATION OF A HEALTHY COMPETITION - J Jopie Gilalo (JURNAL HUKUM DE'RECHTSSTAAT, 2015)
ABSTRACTFair business competition is expected to grow and thrive in the dynamic economy in Indonesia. In accordance with the mandate of the Constitution of 1945 with the characteristics of the economic system in Indonesia is Pancasila which is the basic framework of the government policy to foster and develop the Indonesian economy. The existence of Act No. 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Competition Antitrust Law, provides boundaries for businesses (Enterprises) are prohibited to carry out business activities that are not in accordance with the law. Business Competition Supervisory Commission (KPPU) as the supervisory agency of the implementation of Anti-Monopoly Law provide effectiveness of law enforcement for the business person who violates this law. Although the implementation of the Commission are still many obstacles of some decisions decided by the Commission against business people who commit fraud are not in accordance with the Anti-Monopoly Law, but the decision of the Commission at least be able to provide a deterrent for business people who commit fraud. Keywords : Business Competition, Democracy, Economy